2017
DOI: 10.1159/000484113
|View full text |Cite
|
Sign up to set email alerts
|

Care of the Acute Kidney Injury Survivor

Abstract: While the short-term implications of acute kidney injury (AKI) have been known for many years, far less attention has been paid to the health of AKI survivors. This was perhaps fueled by a prevailing wisdom that if a patient was fortunate enough to survive the primary illness associated with AKI, the prognosis for future health was auspicious. More recently, this dogma was challenged by data suggesting that after an episode of AKI, patients remain at risk of experiencing multiple adverse health outcomes. Great… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…However, the value of the AKI Clinic model needs to be further studied with properly designed interventional studies that focus not only on hard outcomes such as mortality, CKD, or ESRD but also on patient-centered outcomes including quality of life, cardiovascular comorbidity and cognitive function. 18 We believe that the barriers for optimal follow-up of AKI survivors include incomplete awareness of the multiple AKI consequences by the health care team and ineffective education maneuvers for patients and/or caregivers during the hospitalization.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the value of the AKI Clinic model needs to be further studied with properly designed interventional studies that focus not only on hard outcomes such as mortality, CKD, or ESRD but also on patient-centered outcomes including quality of life, cardiovascular comorbidity and cognitive function. 18 We believe that the barriers for optimal follow-up of AKI survivors include incomplete awareness of the multiple AKI consequences by the health care team and ineffective education maneuvers for patients and/or caregivers during the hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…Acute kidney injury survivors were defined as patients who have achieved clinical stability and were discharged from the hospital, irrespective of their degree of kidney recovery. 18 The post-discharge AKI Clinic was established at the University of Kentucky Medical Center in October of 2016 following the model described by Silver and colleagues. 22 The main goal of the AKI Clinic was to evaluate kidney recovery in AKI survivors during the first 90 days post-discharge as this may be informative for their subsequent risk of recurrent AKI or incident/progressive CKD or end-stage renal disease (ESRD).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… 57 Follow-up recommendations ( Figure 1 ) 31 have been proposed that could be integrated into a KDIGO guideline revision. Although it has been suggested that patients be screened at hospital discharge or seen within 1 month of AKI diagnosis, 58 there is no consensus on the optimal strategy and duration of follow-up to improve short- and long-term outcomes.…”
Section: Aki Risk Stratification and Assessmentmentioning
confidence: 99%
“…The overall incidence of AKI is estimated to be 0.2-0.3%, the incidence of AKI in hospitalized patients is 10%, the incidence in intensive care units is 22-67% and the mortality rate is as high as 50-80% (2). In addition, the overall mortality rate of AKI is 60% in adults and 57-66% in children (3). In the USA, ~300,000 individuals succumb to AKI each year.…”
Section: Introductionmentioning
confidence: 99%